The anatomy of agency: Improving academic performance in first‐year university students. Issue 6 (20th January 2022) - Rutenberg, Izaak; Ainscough, Louise; Colthorpe, Kay; Langfield, Tracey
Abstract: The transition from secondary to tertiary education can be challenging, as students must adapt to independent learning. For students in the allied health and nursing disciplines, this transition may coincide with compulsory first‐year courses in anatomy, which are traditionally difficult to master. Students' agency—their capacity to make intentional choices to alter the path of their learning—may play a role in their successful completion of first‐year anatomy courses. This study aimed to develop a measure for agency and to determine whether agency is associated with academic achievement. First‐year students ( n = 131) completed open‐ended questions measuring each aspect of agency. Student responses were quantified using rubrics and then combined to create an overall agency score. Three factors of agency were determined: action, metacognition, and self‐efficacy. Students with higher agency scores were significantly more likely to have higher academic achievement in anatomy compared to students with lower agency scores. The relationship between agency and academic achievement was strongest for action. These results suggest that encouraging students to be active participants in their learning may help them to achieve at university.